Peranan komisi pemberantasan korupsi dalam merealisasikan urus tadbir baik dalam Islam di Indonesia / Afriadi Sanusi - Afriadi, Sanusi (2017)
This research examines the role of the Commission on Combating Corruption to Realize Good Governance from Islamic Perspective in Indonesia. It examines the extent to which the effort and the role of the Commission in fighting corruption and its impact on development and good governance practices in Indonesia. This research is important because the issue of corruption is a problem affecting all countries nowadays. This research is a qualitative research. This researches trying to show how the fighting of corruption can establish good governance from Islamic perspective. The researcher uses library research methodology and documentation in conducting this research. All the data and materials gathered from books, journals, magazines, newspapers, websites, information provided by the Commission, such as annual reports, Journals Integrito, 2013 and 2014 reports of accountability and so on. In building a theoretical framework for this research, status of corruption from Islamic perspectives was discussed followed by a discussion of its’ relation with good governance from Social Science perspective. The issue which was raised is the link between corruption and good governance in Indonesia, KPK’s approaches in fighting corruption, and KPK’s strategies in fighting corruption in 2013 and 2014. The KPK’s strengths and weaknesses as well as its’ improvement efforts in 2014 and 2015 were included in this discussion. This research found that the KPK’s corruption fighting has a positive influence on the development of good governance in Indonesia. This achievement can be measured by through the index of perception of corruption, democracy index, and the index of human resources in Indonesia. The conclusion from this research suggests that the Commission Institution should be maintained because it provides many benefits to the nation. However, the problematic and unproductive leadership and members of the Commission should be transformed for better quality, credibility and integrity of the Commission in the future.